Retrospective comparative study of rigid and flexible ureteroscopy for treatment of proximal ureteral stones - Ehab Mohamad Galal; Ahmad Zaki Anwar; Tarek Khalaf Fath El-Bab; Amr Mohamad Abdelhamid (International Brazilian Journal of Urology)
ABSTRACT Background: We analyzed the outcome and complications of rigid (R-URS) and flexible (F-URS) ureteroscopic lithotripsy for treatment of proximal ureteric stone (PUS). Subjects and methods: Retrospective data of 135 patients (93 males and 42 females) submitted to R-URS and F-URS for treatment of PUS in the period between July 2013 and January 2015 were investigated. (R-URS, group 1) was performed in 72 patients while 63 patients underwent (F-URS, group 2).We compared the 2 groups for success, stone characteristics, operative time, intraoperative and postoperative complications. Results: The overall stone free rate (SFRs) was 49/72 (68%) in group 1 and 57/63 (91%) patients in group 2, (P=0.005). The operative time was shorter in group 1 in comparison to group 2 with statistically significant difference (P=0.005). There was not any statistically significant difference between 2 groups in complication rate (P=0.2). Conclusıon: Both R-URS and F-URS could be a feasible option for treatment of PUS. R-URS is less successful for treatment of PUS and should be used cautiously and with availability of F-URS.